Circular Polarized Dual-Band Wearable Screen-Printed MIMO Antenna Integrated With AMC for WBAN Communications - S. Arulmurugan; T. R. Suresh Kumar; Johan Siden; Zachariah C. Alex (IEEE Open Journal of Antennas and Propagation)
A novel dual-band circularly polarized MIMO wearable antenna is screen-printed on a cotton polyester fabric to operate at 2.45 and 5.8 GHz wireless body area network communications. The MIMO fabric antenna is realized with two circularly polarized wearable antennas arranged in orthogonal directions, which provides a less than −10 dB bandwidth of 400 MHz from 2.2 to 2.6 GHz and 800 MHz from 5.3 to 6.1 GHz, with impedance bandwidth of 17 and 14% for lower and higher bands, respectively. The antenna provides an axial ratio bandwidth (below 3 dB) of 3% from 2.4 to 2.47 GHz and 8% from 5.45 to 5.94 GHz. The proposed MIMO antenna is integrated with an artificial magnetic conductor, which helps to create isolation between the human body and antenna, which also minimizes the specific absorption rate (SAR). The antenna SAR performance is tested on the HUGO model, which gives 0.025, 0.035 W/Kg for 1g tissue at 2.45 and 5.8 GHz. Furthermore, the antenna provides good MIMO characteristics such as envelope correlation coefficient, diversity gain, and channel capacity. The antenna is suitable for flexible wearable applications due to fabric substrate, screen printing, low SAR, and lightweight.